Dimensions of organizational culture and its role in building the personality of the organization, an analytical study in the Department of Research and Development at the Ministry of Higher Education and Scientific Research - Jawad, Lacherer Hasan Ghafil (Eximia, 2022)
Aim to search to me Identify on me level the culture regulatory Prevailing in Research and development department And get acquainted on me level employees in the department restriction search and evaluation level Services through their role in building the personality of the organization that distinguishes it from other organizations , Where the organizational culture was represented by its dimensions (participation in decision-making, teamwork, commitment and respect for time, encouragement of creativity and innovation), while the personality of the organization was represented by its dimensions (decision-making, information, incentives, organizational structure), where an intentional sample of the study population amounted to (33 It consisted of (people’s officials, department managers, assistant general manager, and general manager) and the questionnaire was used as a tool to collect data. used Tools and styles Statistical represented b(the middle Arithmetic,deviation normative ,Relative importance ,Labs link) connect search to me Collection From Results via the program statistic(SSPS). Except that it lack to me style enrichment the work and expand it to form one Species incentives approved as well credit freedom staff enjoyment in to implement mission and assignments functional, and weakness in formation difference Same efficiency High in condition happening crises and adoption my take the decision on me intuition in Solution the problems, Neglecting the organization to provide environment Relevance comfortable help staff on me creativity in generation Thoughts New Around Methods and methods Achievement the work.